Strategic change and transformation: A case study at Malayan Banking Berhad - Ahmad Arshad, Darwina; Ahmad, Hartini; Mustapa, Azrain Nasyrah; Mohtar, Shahimi (2012)
Nowadays the challenges faced by the banking industry are enormous and more challenging because the banks system must cope with an era of rapid change of technology, trends towards greater market orientation and globalization and simultaneously the emerging from a period dominated by cost-cutting, downsizing or downscaling. Overall confidence and stability in the Malaysian financial sector is uncertain.Thus, this scenario reinforces most banks to do better transformation on strategic change.The Malayan Banking Berhad (Maybank) was used as a case study because Maybank is the leading bank in the Malaysian financial services industry.This case study aims to analyze internal factors of Maybank Berhad in determining the achievement of Maybank’s strategic change.